PEMBUATAN TOOLS VALIDASI DATA OLT DAN PELANGGAN TELKOM REGIONAL 3 JAWA BARAT - Maulana, Muhamad Bilal irsa; Iqbal, Muhamad (Direktorat Penelitian dan Pengabdian Masyarakat, Universitas Telkom, 2023)
Telkom Regional 3 West Java RAM Division needs an efficient and fast customer and OLT data validation tool. The data validation process is carried out periodically every month. The validation process requires a lot of time because there is a lot of data to be validated. Therefore, a website-based tool was developed using Microservices technology. Microservice is an architecture where application development is carried out in smaller services, which communicate with each other. This system consists of several small services that function to validate customer data and OLT. Each service can be accessed and run independently, thereby increasing the efficiency and speed of customer and OLT data validation in Telkom regional 3 West Java. Apart from that, this tool can also increase speed and accuracy in validating customer and OLT data by the RAM division. The system development process includes requirements analysis, system design, system implementation, and system testing. Test results show that this system is able to provide good performance in validating customer data and OLT. Overall, the development of the Telkom Regional 3 West Java data validation tools system using Microservices technology is able to increase the efficiency and speed of the customer data validation process, and is able to increase overall system scability..